The fertility-sparing treatment and outcome of epithelioid trophoblastic tumor isolated to lung: a case report and review literature - Huang, Zengshu; Yu, Yingjuan; Wen, Darong; Wang, Nan; Zeng, Liping (Frontiers in Oncology, 2024)
Background: Epithelioid trophoblastic tumor (ETT) is the rarest gestational trophoblastic tumor, with poor response to chemotherapy. Hysterectomy as the cornerstone therapy for early ETT is particularly challenging in reproductive age women who often have a strong desire for fertility preservation. The management of extra-uterine ETT could be even more complicated and inconsistent. Here we reported a case of isolated ETT lesions in lungs managed with thoracic surgery without hysterectomy.Case presentation: A 32-year-old woman presented with amenorrhea for 2 months. Her serum βhuman Chorionic Gonadotropin (hCG) levels fluctuated between 52-75 mIU/mL.The patient underwent removal of intrauterine device and suction and curettage, but only proliferative endometrium was found. Methotrexate was given for a provisional diagnosis of ectopic pregnancy of unknown location while β-hCG had no significant decline. She complained of mild chest pain during past half year and chest computed tomography (CT) showed two mixed ground-glass nodules of 24mm×14.2mm in right upper lobe and 10mm×8mm in right lower lobe, and a thin-walled cavity in posterior segment of left lower lobe. Right upper wedge resection and right lower segmentectomy were performed 3 months later. Pathological examination of pulmonary mass indicated an epithelioid trophoblastic tumor. She was diagnosed with ETT at stage III (with right lung metastasis) according to the FIGO 2000. Her menstrual cycle recovered within 1 month after the first thoracic surgery. However, β-hCG was elevated again to 9 mIU/mL and positron emission tomography/computed tomography (PET/-CT) scans revealed the consolidation of nodule in left lower lobe which enlarged about 1.0cm×1.7cm. Her second pulmonary surgery without hysterectomy was conducted. Followed by 12-month postoperative monitoring, the patient was disease free with negative results of serial serum β-hCG and chest CT.Our case highlights the efficacy of fertility-sparing surgery for isolated ETT in lungs.The surgical management of pulmonary isolated ETT could be individualized under the long-term supervision. Sporadic reports on favorable outcome of extra-uterine ETT with fertility-sparing surgery described in the last decades. The safety of this surgical strategy might be warranted only if enough reliable data accumulated.